IMPACT OF E-PERFORMANCE MANAGEMENT SYSTEM ON PRODUCTIVITY OF SELECTED MANUFACTURING COMPANIES, ABUJA (ABUJA JOURNAL OF BUSINESS AND MANAGEMENT, 2024)
This study investigated the impact of E-Performance Management Systems (E-PMS) on productivity within selected manufacturing companies in Abuja. To determine whether E-PMS influences productivity, three hypotheses were developed based on the research questions and objectives. This study had a population of 235 employees from selected manufacturing companies in Abuja and data were gathered through the administration of copies of questionnaire on 178 respondents. The gathered data were analysed using the simple percentage whilst the hypotheses ere tested using the regression technique. The analysis revealed that E-Performance Management Systems significantly impact the productivity of the selected companies. The study concludes that E-PMS are essential for enhancing the overall performance of manufacturing companies. Based on these findings, it is recommended that organizations invest in the ongoing improvement and effective implementation of their E-Performance Appraisal systems. This should include regular training sessions for both employees and managers to ensure comprehensive understanding of the system, along with periodic reviews to ensure that appraisal criteria remain aligned with the organization’s evolving needs.